Lexicon and word formation in Indonesian Bajo - Nuraini, Chandra (Wacana, Journal of the Humanities of Indonesia, 2010)
This paper1 deals with the phonology and the lexicology of the Indonesian Bajo language and more specifically with the dialect or variant that can be heard all around the Flores Sea in Kangean, South-East Sulawesi, Sumbawa, and Flores. The phonological survey focuses on vowel lengthening, gemination, pre-nasalized phonemes, and sandhi. The second part of this paper proposes an insight into Bajo lexicology, restricted to nominal and verbal derivation.